Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/ejoc.201403021
|View full text |Cite
|
Sign up to set email alerts
|

Photodriven Transfer Hydrogenation of Olefins

Abstract: An improved practical method for the photodriven diimide reduction of olefins was investigated. This catalyst‐free procedure proceeds at ambient temperature, utilizes air as oxidant and a lower hydrazine loading, and produces inert nitrogen gas as the sole byproduct. Several functional groups were tolerated, and in some cases, the reaction was chemoselective. Challenging substrates such as cinnamate ester derivatives and trans‐stilbene were reduced in excellent yields. The small amount of UVA rays emitted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 60 publications
1
24
0
1
Order By: Relevance
“…However, from an (atom‐)economic point of view, the aerobic oxidation of N 2 H 4 is the most attractive source. Since this oxidation is generally very slow, several catalysts, such as Cu15 or Fe salts,16, 17 guanidine derivatives,18 flavin‐based catalysts,19 or even visible light,20 were studied. The generation of diimide in batch by oxidation of hydrazine with O 2 in the absence of a catalyst is also possible, even though significantly longer reaction times in combination with a high excess of hydrazine are required to reduce simple olefins 21…”
Section: Introductionmentioning
confidence: 99%
“…However, from an (atom‐)economic point of view, the aerobic oxidation of N 2 H 4 is the most attractive source. Since this oxidation is generally very slow, several catalysts, such as Cu15 or Fe salts,16, 17 guanidine derivatives,18 flavin‐based catalysts,19 or even visible light,20 were studied. The generation of diimide in batch by oxidation of hydrazine with O 2 in the absence of a catalyst is also possible, even though significantly longer reaction times in combination with a high excess of hydrazine are required to reduce simple olefins 21…”
Section: Introductionmentioning
confidence: 99%
“…[7] More recently hydrazine was successfully used as H2-donor for the uncatalyzed, photodriven transfer hydrogenation of unactivated olefins under ambient conditions in air, with N2 being the sole by-product of the reaction. [8] Mild catalyst-free direct hydrogenation reactions of unsaturated hydrocarbons, however, unknown due to extremely high activation barriers. [8] This is in contrast to the heavier p-block alkene and alkyne analogues, in which the frontier molecular orbitals are separated by more modest energies, making them more reactive toward small molecules.…”
mentioning
confidence: 99%
“…[8] Mild catalyst-free direct hydrogenation reactions of unsaturated hydrocarbons, however, unknown due to extremely high activation barriers. [8] This is in contrast to the heavier p-block alkene and alkyne analogues, in which the frontier molecular orbitals are separated by more modest energies, making them more reactive toward small molecules. In 2005 Power and co-workers showed that a terphenylsupported digermyne underwent room temperature hydrogenation at atmospheric pressure, albeit unselectively, yielding a mixture of mono-, di-and trihydrogenated species.…”
mentioning
confidence: 99%
“…Penghidrogenan menggunakan mangkin selenium dipilih kerana berdasarkan kajian lepas (Ou et al 2016;Schulz et al 2012), pengoksidaan hidrazin oleh selenium menghasilkan unit cis-diimida yang dominan (Kondo et al 1977;Leow et al 2014). Penghidrogenan stereospesifik ini penting bagi mendapatkan produk terhidrogen yang diingini apabila penurunan diimida dapat berlaku secara lengkap.…”
Section: Pengenalanunclassified